Optimal control problems without terminal constraints: The turnpike property with interior decay - Gugat, Martin; Lazar, Martin (Zielona Góra: Uniwersytet Zielonogórski)
We show a turnpike result for problems of optimal control with possibly nonlinear systems as well as pointwise-in-time state and control constraints. The objective functional is of integral type and contains a tracking term which penalizes the distance to a desired steady state. In the optimal control problem, only the initial state is prescribed. We assume that a cheap control condition holds that yields a bound for the optimal value of our optimal control problem in terms of the initial data.
Keywords: optimal control; turnpike property; system with hyperbolic PDEs; interior decay